Comparação do nível de dor femoropatelar, atividade física e qualidade de vida entre adolescentes do sexo feminino e masculino - Waiteman, Marina Cabral [UNESP]; Coura, Maira Bergamaschi [UNESP]; Araújo, Cynthia Gobbi Alves [UNESP]; Briani, Ronaldo Valdir [UNESP]; Silva, Danilo de Oliveira [UNESP]; de Azevedo, Fábio Mícolis [UNESP] (EDIPUCRS, 2017)
Aims: To compare the level of pain, physical activity, and quality of life of female and male adolescents with patellofemoral pain. Methods: A total of 46 female adolescents and 46 male adolescents aged 12 to 18 years were recruited from public and private schools in the town of Presidente Prudente, São Paulo, Brazil. To be included in the study, adolescents needed to report knee pain of insidious onset, exacerbated in some activities, and lasting for at least 6 weeks. In addition, adolescents should report worse pain over the previous week of at least 30 mm on the Visual Analog Scale and could not show signs, symptoms or any occurrence of any other knee dysfunction. The participants were requested to mark their self-reported knee pain in the last month on a Visual Analog Scale. The level of physical activity was evaluated by the Baecke Questionnaire of Habitual Physical Activity and the quality of life subscale of the Knee Outcome in Osteoarthritis Survey questionnaire was used to investigate the participants' quality of life. The independent t-test was used to find differences between the groups regarding the level of physical activity, quality of life, and knee pain. Results: According to the Visual Analog Scale, male adolescents presented a level of knee pain of 5.1 ± 1.4 in the previous month and female adolescents, of 4.4 ± 1.6 (p = 0.029). The physical activity score was 8.8 ± 1.3 for male adolescents and 7.5 ± 1.6 for female ones (p < 0.001). The quality of life subscale scores were 77.9 ± 19.0 for adolescent girls and 70.8 ± 13.5 for male adolescents (p=0.042). Conclusions: Among adolescents with patellofemoral pain, males had a higher level of knee pain, higher level of physical activity, and lower quality of life compared to female adolescents.
Comparison of the level of patellofemoral pain, physical activity, and quality of life between female and male adolescents
Keywords: Adolescent; Patellofemoral pain syndrome; Quality of life